2021
DOI: 10.1111/cbdd.13963
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of novel fasudil derivatives as potent antibreast cancer agent that improves intestinal flora and intestinal barrier function in rats

Abstract: This study was conducted to develop novel fasudil derivatives after incorporation of substituted thiazoles as potent anti-breast cancer (BC) agents. The compounds were developed using a facile synthetic route in excellent yields. The entire set of developed compounds was tested for inhibitory activity against rho-associated coiled-coil kinase (ROCK; ROCK1 and ROCK2) kinase, where they exhibit potent and selective inhibition of ROCK1 as compared to ROCK2. The most potent ROCK2 inhibitor, compound 6h significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Intestinibacter, a genus of gut bacteria that is not yet widely understood, and its association with renal malignant tumors has also been the subject of recent research. There is a positive causal effect between the relative abundance of Intestinibacter in the intestinal ora and the development of renal malignant tumors, i.e., individuals with a relatively higher abundance of Intestinibacter are more likely to develop renal malignant tumors 57 . Intestinibacter may be associated with the development of renal malignancies through pathways such as metabolites, activation of immune responses, or in uence on cell signaling pathways 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Intestinibacter, a genus of gut bacteria that is not yet widely understood, and its association with renal malignant tumors has also been the subject of recent research. There is a positive causal effect between the relative abundance of Intestinibacter in the intestinal ora and the development of renal malignant tumors, i.e., individuals with a relatively higher abundance of Intestinibacter are more likely to develop renal malignant tumors 57 . Intestinibacter may be associated with the development of renal malignancies through pathways such as metabolites, activation of immune responses, or in uence on cell signaling pathways 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Compound 31 was also active in a scratch assay performed on human breast cancer MDA‐MB 231 cells, 87 By introducing the pyridine‐thiozole group into Fasudil, Liang observed that compound 32 showed potent inhibition of ROCK. The most potent compound 32a could significantly inhibit the viability of breast cancer cells (MCF‐7) and improve intestinal flora and intestinal barrier function in rats 88 . Domokos et al reported that 1‐substituted tetrahydroisoquinoline (compound 33 ) and its ring‐opening analog (compound 34 ) exhibited ROCK II inhibitory activity similar to Y‐27632, and relaxed the 20‐day pregnant and parturient rat uterus with greater potency as compared to Fasudil 89 .…”
Section: Synthetic Rock Inhibitorsmentioning
confidence: 99%
“…The most potent compound 32a could significantly inhibit the viability of breast cancer cells (MCF-7) and improve intestinal flora and intestinal barrier function in rats. 88 Fasudil. 89 Utilizing modern computer-aided drug design techniques, Kesar et al found that quinoline compound 35 exhibited potent ROCK II inhibition with an IC 50 value of 8.02 nM.…”
Section: Isoquinolines and Quinolinesmentioning
confidence: 99%
“…Shang et al [ 159 ] reported that chondroitin sulfate (SCS) in sturgeon might inhibit the growth of CRC by regulating the gut microbiota and altering the manufacture of certain amino acids. Liang et al [ 160 ] demonstrated the development of a novel fasudil derivative, which can improve the gut microbiota and the function of the intestinal barrier in rats, and may act as a potent anti-breast cancer (BC) drug. Emerging studies have indicated that next-generation probiotics (NGPs) have beneficial effects in preventing carcinogenesis and provide new promising therapeutic options for cancer patients.…”
Section: Radiotherapy For Cancer Based On the Gut Microbiotamentioning
confidence: 99%